1989
DOI: 10.1111/j.1469-8137.1989.tb02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different inocula of vesicular‐arbuscular mycorrhizal fungi on manganese content and concentration in red clover (Trifolium pratense L.) plants

Abstract: .ManK^incsc a\'ailahtltt\' in .soils iticrcascs witli sotl acidit\\ llu' clement reachitiLi; toxic lc\cls for jilatit fj;r()vvth \n sotnc situations. 'I'his toxic ellcct ts usualK o\ crcome hy the ailtlitioti of lime. Iti fact, tiiati^ancsc toxtctty ts rarely ohscrvcci tti )irotiuctt\-c areas (Smtth & I'xltncadcs, l*'S,'i), \c\ crtlicioss, tiiatiy acici sotls cotitaiti ctioufjjli niatiLjaticsc to recincc platit growth but not to load to clc\ clo]itnctit of toxicitN' sytiiptotiis in tlif phmt. The coniplexinf^ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The concentration of Mn decreased equally in the shoot and roots of mycorrhizal plants (Fig. 3) as has been shown for red clover plants (Arines et al, 1989). The causes of such decline are not clear.…”
Section: Discussionmentioning
confidence: 90%
“…The concentration of Mn decreased equally in the shoot and roots of mycorrhizal plants (Fig. 3) as has been shown for red clover plants (Arines et al, 1989). The causes of such decline are not clear.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to the reports above, Jones et al (1986) reported that mycorrhizae reduced Ca uptake and increased the Al sensitivity of paper birch (Betula papyrifera Marsh) and jack pine (Pinus banksiana Lamb). Arines et al (1989) reported that mycorrhizae decreased Mn concentrations in shoots and roots of plants in three acid soils.…”
Section: B Using Stress Tolerant Plantsmentioning
confidence: 98%
“…V A-mycorrhizal hyphae are effective in uptake particularly of P (Rhodes and Gerdemann, 1975;Li et al 1991), Zn (Swaminathan and Verma 1979;Kothari et al 199Ib), Cu (Gildon and Tinker, 1984;Li et al 1991), and N (Ames et al 1983;George et al 1992). It has also been reported that V AM infection may decrease the uptake of Mn (Arines et al 1989;Kothari et al 199Ia). Among the nutrients, P has been subjected to the largest number of studies because improved growth by V AM infection is most often correlated with higher P uptake by the plant (Bolan 1991).…”
mentioning
confidence: 99%